Dearborn Drug and Chemical Works hospitality suite - Dearborn Chemical Company (1910)
Postcard with front view of the Dearborn Drug and Chemical Works hospitality suite located at Young's Million Dollar Pier in Atlantic City, New Jersey. The individuals visible in the photograph are unidentified. Dearborn maintained a permanent hospitality suite at the pier to market the company's products and services to railroad executives who commonly attended Master Car Builders' and Master Mechanics' Conventions. Founded in 1887, the Dearborn Drug and Chemical Works (later Dearborn Chemical Company) was a corporate ancestor of BetzDearborn, Incorporated best known for manufacturing water treatment chemicals for use in boilers, cooling towers, and steam locomotives.
Keywords: Employees; Chemical industry; Dearborn Chemical Company; Trade shows; Water purification chemicals industry; Corporations